Plasma extracellular vesicles released after severe burn injury modulate macrophage phenotype and function. Issue 1 (3rd August 2021) - Willis, Micah L; Mahung, Cressida; Wallet, Shannon M; Barnett, Alexandra; Cairns, Bruce A; Coleman, Leon G; Maile, Robert
Abstract: Extracellular vesicles (EVs) have emerged as key regulators of immune function across multiple diseases. Severe burn injury is a devastating trauma with significant immune dysfunction that results in an ∼12% mortality rate due to sepsis-induced organ failure, pneumonia, and other infections. Severe burn causes a biphasic immune response: an early (0–72 h) hyper-inflammatory state, with release of damage-associated molecular pattern molecules, such as high-mobility group protein 1 (HMGB1), and proinflammatory cytokines (e.g., IL-1β), followed by an immunosuppressive state (1–2+ wk post injury), associated with increased susceptibility to life-threatening infections. We have reported that early after severe burn injury HMGB1 and IL-1β are enriched in plasma EVs. Here we tested the impact of EVs isolated after burn injury on phenotypic and functional consequences in vivo and in vitro using adoptive transfers of EV. EVs isolated early from mice that underwent a 20% total body surface area burn injury (burn EVs) caused similar hallmark cytokine responses in naïve mice to those seen in burned mice. Burn EVs transferred to RAW264.7 macrophages caused similar functional (i.e., cytokine secretion) and immune gene expression changes seen with their associated phase of post-burn immune dysfunction. Burn EVs isolated early (24 h) induced MCP-1, IL-12p70, and IFNγ, whereas EVs isolated later blunted RAW proinflammatory responses to bacterial endotoxin (LPS). We also describe significantly increased HMGB1 cargo in burn EVs purified days 1 to 7 after injury. Thus, burn EVs cause immune outcomes in naïve mice and macrophages similar to findings after severe burn injury, suggesting EVs promote post-burn immune dysfunction. Graphical Abstract: Extracellular vesicles released into the plasma after severe burn injury transduce dysfunctional immune signaling in naive mice and macrophages similar to the clinical course after burn.